Syntactic Errors in Indonesian EFL Students' Narrative Essay Writing - Novendra Dewanto (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates syntactic errors in the narrative essays of Indonesian EFL students, specifically third-semester English Literature students at Universitas Teknokrat Indonesia. Writing is among the most demanding skills in language learning, requiring mastery of grammar and sentence structure in addition to idea organization. Using a descriptive qualitative design, ten student essays were analyzed and classified based on the Surface Strategy Taxonomy (Dulay, Burt, & Krashen, 1982), which includes omission, addition, misformation, and misordering. A total of 101 syntactic errors were identified: misformation (31.7%) was the most frequent, followed by omission (28.7%), misordering (27.7%), and addition (13.9%). The results revealed that omission errors were mainly caused by interlingual transfer from Indonesian, while misformation and misordering resulted from intralingual factors such as overgeneralization and incomplete rule acquisition. These findings confirm that syntactic errors are systematic and developmental in nature, representing the learners’ interlanguage progression rather than failure. Pedagogically, the study underscores the need for focused instruction on verb tense, auxiliary usage, article application, and word order, supported by contrastive and technology-assisted approaches. The study concludes that understanding learners’ syntactic errors is essential for designing effective grammar pedagogy in EFL writing, allowing errors to serve as valuable indicators of language development rather than mere deficiencies.